Thermally rearranged (TR) HAB-6FDA nanocomposite membranes for hydrogen separation. (24th July 2020) - Patel, A.K.; Acharya, N.K.
Abstract: Thermally rearranged (TR) polymers exhibited a good balance of high permeability and high selectivity. For this purpose HAB-6FDA polyimide was synthesized from 3, 3 dihydroxy-4, 4-diamino-biphenyl (HAB) and 2, 2-bis-(3, 4-dicarboxyphenyl) hexafluoro propane dianhydride (6FDA) by chemical imidization. Initially, the sample was modified from pure polymer to silica nanofiller doped polymer membrane. Further the modification was done by thermal rearrangement reaction at 350 °C temperature. This modification causes a mass loss in polymer structure and therefore enhances the fractional free volume (FFV). The gases used for the permeation test were H2, CO2, N2 and CH4 . Selectivity was calculated for H2 /CO2, H2 /N2 and H2 /CH4 gas pairs and plotted in the Robeson's 2008 upper bound and compared with reported data. The transport properties of these gases have been compared with the unmodified membrane. Permeability of all the gases has increased to that of unmodified polymer membrane. Thermally rearranged polymer nanocomposite exhibits higher gas permeability than that of silica doped and pure polymer. Also the selectivity for H2 /CO2 and H2 /N2 gas pairs exceeds towards Robeson's upper bound limit. It crosses this limit dramatically for H2 /CH4 gas pair. Polymer nanocomposite can be utilized to obtain high purity hydrogen gas for refinery and petrochemical applications. Highlights: SiO2 incorporated thermally rearranged (TR) polyimide exhibits promising substance for hydrogen separation. Selectivity exceeds toward Robeson's upper bound for H2 /CO2 and H2 /N2 gas pairs. For H2 /CH4 gas pair, selectivity crosses Robeson's 2008 upper bound. Dispersion of nanofiller improves gas permeability.